UPAR regulates bronchial epithelial repair in vitro and is elevated in asthmatic epithelium. Issue 6 (3rd December 2011) - Stewart, Ceri E; Nijmeh, Hala S; Brightling, Christopher E; Sayers, Ian
Abstract : Background: The asthma-associated gene urokinase plasminogen activator receptor (uPAR) may be involved in epithelial repair and airway remodelling. These processes are not adequately targeted by existing asthma therapies. A fuller understanding of the pathways involved in remodelling may lead to development of new therapeutic opportunities. uPAR expression in the lung epithelium of normal subjects and patients with asthma was investigated and the contribution of uPAR to epithelial wound repair in vitro was studied using primary bronchial epithelial cells (NHBECs). Methods: Bronchial biopsy sections from normal subjects and patients with asthma were immunostained for uPAR. NHBECs were used in a scratch wound model to investigate the contribution of the plasminogen pathway to repair. The pathway was targeted via blocking of the interaction between urokinase plasminogen activator (uPA) and uPAR and overexpression of uPAR. The rate of wound closure and activation of intracellular signalling pathways and matrix metalloproteinases (MMPs) were measured. Results: uPAR expression was significantly increased in the bronchial epithelium of patients with asthma compared with controls. uPAR expression was increased during wound repair in monolayer and air-liquid interface-differentiated NHBEC models. Blocking the uPA–uPAR interaction led to attenuated wound repair via changes in Erk1/2, Akt and p38MAPK signalling. Cells engineered to have raised levels of uPAR showed attenuated repair via sequestration of uPA by soluble uPAR. Conclusions: The uPAR pathway is required for efficient epithelial wound repair. Increased uPAR expression, as seen in the bronchial epithelium of patients with asthma, leads to attenuated wound repair which may contribute to the development and progression of airway remodelling in asthma. This pathway may therefore represent a potential novel therapeutic target for the treatment of asthma.